The impacts of final delivery solutions on e-shopping usage behaviour: The case of Shenzhen, China. Issue 1 (8th January 2018) - Xiao, Zuopeng; Wang, James J.; Liu, Qian
Abstract : Purpose: The purpose of this paper is to examine the effects of final delivery solutions on e-shopping usage behaviour by modelling their interaction across residents living in different neighourhoods with availabilities of different facilities, including automated parcel stations (APSs), collection and delivery points (CDPs), and the direct-to-home delivery stations of parcel express firms (PEFs). Design/methodology/approach: The study is based on a survey on e-shopping behaviour and delivery awareness. A mixed structural equation model is used to predict the interactions among availability of final delivery facilities (AFDF), level of satisfaction with delivery services and e-shopping usage after controlling individual socioeconomic attributes and retail environment. Findings: Compared with AFDF, individual socioeconomic attributes are the most influential factors contributing to e-shopping spending and frequency. Improving AFDF has only a slight effect on e-shopping spending, while a larger impact on e-shopping frequency and perceived satisfaction to delivery services is observed. The quantity of PEF delivery stations has a relatively large influence on e-shopping usage but the effects of APSs and CDPs are not as strong as expected. Research limitations/implications: The causality between final delivery solutions and e-shopping behaviour can be further tested by using social experiments or longitudinal data. Practical implications: All findings will help business and public policy decision makers to derive a balanced and effective deployment of final delivery solutions, which is also referential for other emerging markets similar to China. Originality/value: This study theoretically contributes to the international literature by examining the heterogeneous effects of final delivery solutions on different aspects of e-shopping engagement.